Climate change effects on northern Great Lake (USA) forests: A case for preserving diversity. Issue 2 (28th February 2014) - Duveneck, Matthew J; Scheller, Robert M; White, Mark A; Handler, Stephen D; Ravenscroft, Catherine
Abstract : Under business as usual (BAU) management, stresses posed by climate change may exceed the ability of Great Lake forests to adapt. Temperature and precipitation projections in the Great Lakes region are expected to change forest tree species composition and productivity. It is unknown how a change in productivity and/or tree species diversity due to climate change will affect the relationship between diversity and productivity. We assessed how forests in two landscapes (i.e., northern lower Michigan and northeastern Minnesota, USA) would respond to climate change and explored the diversity‐productivity relationship under climate change. In addition, we explored how tree species diversity varied across landscapes by soil type, climate, and management. We used a spatially dynamic forest ecosystem model, LANDIS‐II, to simulate BAU forest management under three climate scenarios (current climate, low emissions, and high emissions) in each landscape. We found a positive relationship between diversity and productivity only under a high emissions future as productivity declined. Within landscapes, climate change simulations resulted in the highest diversity in the coolest climate regions and lowest diversity in the warmest climate region in Minnesota and Michigan, respectively. Simulated productivity declined in both landscapes under the high emissions climate scenario as species such as balsam fir ( Abies balsamea ) declined in abundance. In the Great Lakes region, a high emissions future may decrease forest productivity creating a more positive relationship between diversity and productivity. Maintaining a diversity of tree species may become increasingly important to maintain the adaptive capacity of forests.